Reduced occludin and claudin-7 expression is associated with urban locations and exposure to second-hand smoke in allergic rhinitis patients - Nur Husna, Siti Muhamad (Sci Rep, 2021)
The breakdown of nasal epithelial barrier occurs in allergic rhinitis (AR) patients. Impairment of cell junction molecules including tight junctions (TJs) and desmosomes plays causative roles in the pathogenesis of AR. In this study, we investigated the transcript expression levels of TJs including occludin (OCLN), claudin-3 and -7 (CLDN3 and CLDN7), desmoglein 3 (DSG3) and thymic stromal lymphopoietin (TSLP) in AR patients (n = 30) and non-allergic controls (n = 30). Nasal epithelial cells of non-allergic controls and AR patients were collected to examine their mRNA expression levels, and to correlate with clinico-demographical and environmental parameters. We demonstrated that the expression of OCLN (p = 0.009), CLDN3 (p = 0.032) or CLDN7 (p = 0.004) transcript was significantly lower in AR patients compared with non-allergic controls. No significant difference was observed in the expression of DSG3 (p = 0.750) or TSLP (p = 0.991) transcript in AR patients compared with non-allergic controls. A significant association between urban locations and lower OCLN expression (p = 0.010), or exposure to second-hand smoke with lower CLDN7 expression (p = 0.042) was found in AR patients. Interestingly, none of the TJs expression was significantly associated with having pets, frequency of changing bedsheet and housekeeping. These results suggest that defective nasal epithelial barrier in AR patients is attributable to reduced expression of OCLN and CLDN7 associated with urban locations and exposure to second-hand smoke, supporting recent findings that air pollution represents one of the causes of AR.